Depth-wise Variation of Cationic Micronutrients in Lateritic Soil under Rice, Non-rice and Fallow Land Ecology - Chatterjee, Shubhasish; Kundu, Manik Chandra (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted from May, 2022 to February, 2023 in Birbhum district of West Bengal, India to examine variations of DTPA extractable Zn, Cu, Fe, and Mn content and their correlations with soil physico-chemical properties in lateritic soil across different depths (0–15 cm, 15–30 cm, and 30–45 cm) and agricultural ecologies (rice, non-rice, and fallow lands). Ninety soil samples (10 locations×3 ecosystems×3 depths) were collected and analysed. Soils varied from strong to moderate acidity, low salinity; surface soil had lower pH, while sub-surface was higher. Organic carbon content was low to moderate. Overall, the Zn, Cu, Fe, and Mn contents and soil physico-chemical properties varied across soil ecologies and depths. Irrespective of soil ecologies, their mean values were highest at 0–15 cm and lowest in 30–45 cm soil depth, indicating decreasing trend with increased depth. Irrespective of depths, fallow land exhibited the highest levels of the Zn, Cu, Fe, and Mn. However, the lowest Zn content was recorded in rice soil ecologies, and that of the lowest Cu, Fe, and Mn were recorded in non-rice ecologies. DTPA extractable Zn correlated positively with pH, EC, OC, CEC, and negatively with available N. DTPA extractable Fe negatively correlated with K2O, while Mn correlated positively with OC, CEC, and available N, negatively with clay. DTPA extractable Cu correlated negatively with clay. The results suggested enhancing integrated land management and micronutrient fertilization to improve soil fertility and agricultural productivity lateritic soils of West Bengal, India.